Survey of trypanosoma (Kinetoplastida: Trypanosomatidae) infection in monte negro municipality, state of rondônia, western amazon, with first record of t. evansi in the state - Bilheiro, Adriana Benatti; Camargo, Juliana Souza Almeida Aranha; Zamarchi, Tallita Beatriz de Oliveira; Tonholo, Caio; Bassin, Henrique Caetano Mingoranci; Sussuarana, Israelita Tihara de Almeida; Henriques, Augusto Loureiro; Camargo, Luis Marcelo Aranha (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Introduction: Trypanosomes can infect humans and animals. This is the first record of the occurrence of Trypanosoma evansi in Rondônia. Methods: Blood samples were collected from 7 dogs and 22 humans. Furthermore, triatomines and tabanids were collected. Results: It was observed that 42.8% of the dogs tested positive for T. evansi and 14.3% presented mixed infection; 15% of the triatomines tested positive for flagellates identified as T. cruzi TCI (3 specimens), T. cruzi TCI, and T. rangeli (1 specimen), and one with T. cruzi TCV. Two tabanids were infected with T. theileri. Conclusions: These findings may benefit vector control strategies. © 2019, Sociedade Brasileira de Medicina Tropical. All rights reserved.
Keywords: Anemia; Blood Sampling; Chagas Disease; Dog; Enzyme-linked Immunosorbent Assay; Flagellate; Health Survey; Human; Immunofluorescence Test; Leishmaniasis; Malaria; Mixed Infection; Nonhuman; Parasite Transmission; Parasitemia; Physical Examination; Rna Sequencing; Rondonia; Surra; Tetranychus Evansi; Trypanosoma Cruzi; Weakness; Animals; Blood; Chagas Disease; Classification; Health Survey; Insect Vector; Isolation And Purification; Parasitology; Rhodnius; Trypanosoma; Protozoon Antibody; Animal; Antibodies, Protozoan; Chagas Disease; Dogs; Health Surveys; Humans; Insect Vectors; Rhodnius; Trypanosoma